Association of selected mirnas in susceptibility and resistance to tuberculosis - Nor, Norazmi Mohd (Pusat Pengajian Kesihatan, 2015)
MicroRNAs (miRNAs) play an important role in the pathogenesis of various diseases. Hence human miRNAs may be able to inhibit the replication and survival of Mycobacterium tuberculosis (Mtb) genes in the human host. Mutations within miRNAs can alter their target selection, thereby preventing them from inhibiting Mtb genes and may augment host susceptibility to the disease. This study was undertaken to investigate the genetic ( association of pulmonary TB with six human miRNAs namely: hsa-miR-370, hsa-miR-520d, hsa-miR-154, hsa-miR-497, hsa-miR-758 and hsa-miR-593, which have been predicted to interact with Mtb genes. The objective of the study is to determine possible sequence variation of selected miRNA genes that are potentially associated with the inhibition of critical Mtb genes in TB patients (n=33) and healthy individuals (n=38). There is no sequence variation in all the six human miRNAs in TB patients and healthy contacts when comparing the sequence with the reference sequence available at [http://www.mirbase.org]. The human miRNAs hsa-miR-370, hsa-miR-520d, hsa-miR-154, hsa-miR-497, hsa-miR-758 and hsa-miR- 593 may not be involved directly in the susceptibility or resistance to tuberculosis.